2012
DOI: 10.1097/01.xha.0000415089.15301.51
|View full text |Cite
|
Sign up to set email alerts
|

Possible impact(s) of cell phone electromagnetic radiation on human sperm parameters

Abstract: BackgroundEpidemiological in-vitro studies have highlighted the possibility that exposure to radiofrequency electromagnetic waves emitted from cell phones may negatively affect seminal parameters through altering the DNA integrity of sperm and releasing reactive oxygen species (ROS). PurposeTo determine the hazardous effects of using a cell phone on semen quality in correlation with DNA damage and the release of ROS. Patients and methodsThe study was carried out at the Department of Dermatology and Andrology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The latter effect is postulated to increase the production of the ROS (reactive oxygen species) and this may lead to DNA damage. These outcomes we identified in the same study group with longer time of EMR exposure in our previous work [3] . Regarding the thermal effects “may be largely due to the heat generated by the handsets rather than the RF-EMR, since the EMR frequencies released from cell phones are thought to have negligible heating effects” [11] , [31] .…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The latter effect is postulated to increase the production of the ROS (reactive oxygen species) and this may lead to DNA damage. These outcomes we identified in the same study group with longer time of EMR exposure in our previous work [3] . Regarding the thermal effects “may be largely due to the heat generated by the handsets rather than the RF-EMR, since the EMR frequencies released from cell phones are thought to have negligible heating effects” [11] , [31] .…”
Section: Discussionmentioning
confidence: 66%
“…Semen samples were collected after 3–5 days of abstinence, liquefied for 30 min at 37 °C and analyzed within 60 min after ejaculation according to WHO guidelines; 2010 [14] . The detailed procedure has been described previously [3] . A computer-assisted semen analyzer (Hamilton Thorne, HTM-IVOS, Version 12, Baumann Medical AG, Wetzikon, Switzerland), was used for sperm concentration and kinetic measurements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were also reported by Agarwal et al [16] in their observational study on the effect of cell phone use on the semen parameters of men attending infertility clinics. Moreover, Mostafa et al [17] reported that the duration of cell phone use correlated negatively with the proportion of grade A and grade B sperm motility but correlated positively with the proportion of grade C and grade D motility.…”
Section: Discussionmentioning
confidence: 96%
“…However, studies designed to measure malonaldehyde levels and superoxide dismutase activity have reported conflicting results [22]. Recent studies on human semen also suggested increased ROS production in human semen due to cell phone radiation [8,17]. Oxidative stress has been known to limit the motility and fertilizing potential of human spermatozoa through the induction of peroxidase damage to the sperm plasma membrane [23].…”
Section: Discussionmentioning
confidence: 96%